2020
DOI: 10.3897/compcytogen.v14i3.53367
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and reproductive features of some Oriental and Australasian scale insects (Homoptera, Coccinea)

Abstract: Fourteen species of scale insects from the families Margarodidae s.l., Pseudococcidae, Eriococcidae, and Coccidae were investigated for the first time in respect to karyotypes, genetic systems, modes of reproduction and general anatomy of the female reproductive system. One of the studied species, Steatococcus samaraius Morrison, 1927, showed hermaphroditic reproduction of the female-like specimens, the other species demonstrated bisexual reproduction with a peculiar “Lecanoid” heterochromatinization of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The study had been reported by Dammerman (1929), Wirjati (1958;1959), and Kalshoven (1981), then continued by Reyne (1954;1957;1961;1965), Muniappan et al (2008;, Sartiami et al (2016), Gavrilov-Zimin (20132017;2019;2020; and Zarkani et al (2020;, which have made several additional records to the scale insect fauna. Generally, over 16 years the number of described scale insect species in Indonesia has increased slowly by 53 species (Garcia et al 2016).…”
Section: Introductionmentioning
confidence: 84%
“…The study had been reported by Dammerman (1929), Wirjati (1958;1959), and Kalshoven (1981), then continued by Reyne (1954;1957;1961;1965), Muniappan et al (2008;, Sartiami et al (2016), Gavrilov-Zimin (20132017;2019;2020; and Zarkani et al (2020;, which have made several additional records to the scale insect fauna. Generally, over 16 years the number of described scale insect species in Indonesia has increased slowly by 53 species (Garcia et al 2016).…”
Section: Introductionmentioning
confidence: 84%
“…The exact reproduction strategy of M. hellenica remains unknown. Parthenogenesis is frequently observed in Hemiptera; however, scales demonstrate the most abundant variety of reproduction strategies [ 73 ], and the identification of the reproduction system of parthenogenetic species is considered a challenging task [ 74 ], with reproductive parasites and endosymbiotic bacteria further complicating the reproduction system’s identification [ 26 ]. For the first time in Greece, males, females, and 3 rd -instar nymphs of M. hellenica were encountered at the same time of the year (January to late March) for two consecutive years (2021 and 2022), although males were found in low numbers compared to females, similarly to other coccids, which produce a sex ratio of 5%:95% (males:females) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asexual reproduction would lead sexually reproduced natural enemies to become proficient at handling the defense mechanisms of a single clone, while their beneficiaries’ own capabilities would be continuously improved [ 85 ]. Furthermore, some species exhibit both sexual and parthenogenetic lineages on different hosts or in different geographical regions [ 24 , 74 , 86 ], with parthenogenetic populations often living within distinct ranges, such as marginal habitats, or at a higher latitude or altitude than sexual lineages [ 87 , 88 , 89 ]. Jensen et al [ 90 ] suggested that sexual populations, usually found at the central part of the range of the infestation, act as sources of populations choosing asexual reproduction, which are found in the marginal regions of infestations.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome numbers have been reported for 506 species of scale insects belonging to 15 families (reviewed by Gavrilov 2007 and Gavrilov-Zimin et al 2015 ; see also Gavrilov-Zimin 2016 , 2017 , 2018b , 2020 ), thus comprising about 6% of the total number of coccid species described to date. The lowest chromosome number, 2n=4, is found in 21 species of the tribe Iceryini ( Margarodidae ) and in several species of the endemic Australian gall-inducing felt-scale genus Apiomorpha ( Eriococcidae ), while the highest number, 2n≈192, is found in Apiomorpha macqueeni Froggatt, 1929 ( Hughes-Schrader 1948 ; Cook 2000 , 2001 ; see for review Gavrilov 2007 ).…”
Section: Review and Discussionmentioning
confidence: 99%
“… The mapping of diploid autosome numbers, male sex chromosome systems, and both modal and putative ancestral states of these characters onto phylogenetic tree of Paraneoptera . The phylogenetic tree is based on Shcherbakov and Popov (2002) , Kluge (2020) , and Gavrilov-Zimin (2020 a), with modifications. Putative ancestral autosome numbers (2n) are indicated by black solid circles (●); putative ancestral sex chromosome systems are indicated by black solid squares (■).…”
Section: Review and Discussionmentioning
confidence: 99%